2021
DOI: 10.1007/s12028-021-01254-9
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Blood Pressure Lowering and DWI Lesions in Intracerebral Hemorrhage: Exploratory Analysis of the ATACH-2 Randomized Trial

Abstract: Background: With the increasing use of magnetic resonance imaging in the assessment of acute intracerebral hemorrhage, diffusion-weighted imaging hyperintense lesions have been recognized to occur at sites remote to the hematoma in up to 40% of patients. We investigated whether blood pressure reduction was associated with diffusionweighted imaging hyperintense lesions in acute intracerebral hemorrhage and whether such lesions are associated with worse clinical outcomes by analyzing imaging data from a randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Besides the primary brain injury, the parenchymal hematoma triggers a series of adverse events causing secondary injury, which plays an essential role in neurological impairment. 25 , 26 , 27 According to the body of literature to date, the presence of DWILs may indicate advanced cerebral small vessel disease burden, which suggests severe endothelial failure, 28 , 29 reduced connectivity of the brain, 30 and susceptibility to the cytokines and prothrombotic milieu generated by a hematoma, 31 , 32 , 33 all of which may affect post‐ICH recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the primary brain injury, the parenchymal hematoma triggers a series of adverse events causing secondary injury, which plays an essential role in neurological impairment. 25 , 26 , 27 According to the body of literature to date, the presence of DWILs may indicate advanced cerebral small vessel disease burden, which suggests severe endothelial failure, 28 , 29 reduced connectivity of the brain, 30 and susceptibility to the cytokines and prothrombotic milieu generated by a hematoma, 31 , 32 , 33 all of which may affect post‐ICH recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that underlying chronic small vessel disease, particularly hypertensive small vessel disease, may predispose certain patients to encountering these DWI ischemic lesions, perhaps independently of acute blood pressure changes, and potentially related to microthrombosis. 1,3,5,23–26 Our results appear to provide novel evidence to suggest a plausible role of higher baseline hemoglobin concentrations as a risk factor associated with DWI lesions in patients with acute ICH. It is known that higher hemoglobin concentrations enhance hemostasis and can provoke thrombosis in settings of vascular injury 8 and have relevant associations with ischemic stroke.…”
Section: Discussionmentioning
confidence: 54%
“…However, the number of patients with hypertension did not differ between groups with and without DWI+ lesions. Furthermore, a recent individual patient data meta-analyses investigated ICH-related DWI+ lesions, blood pressure control, and outcomes, and did not find any associations ( 2 ), and a recent randomized controlled trial demonstrated that intensive acute blood pressure lowering did not lower the frequency of DWI+ lesions in ICH-patients ( 13 ), Alternatively, some hemorrhages might be caused by the hemorrhagic transformation of DWI+ lesions ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%